Interactive Reading for Non-Conventional Spaces in Educational Institutions (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2024)
The research proposed a recreational-pedagogical program that allowed promoting interactive reading in unconventional spaces. Through various authors, the importance of pedagogical activities in unconventional spaces is highlighted. The methodology was qualitative, a pedagogical action research design. Key Informant (9). The semi-structured interview and the interview script were used. Results: Lack of reading habits in students, little support and use of recreational activities by teachers; Because of the family, there is no motivation to acquire reading. Conclusion, with strategies and an unconventional space, the development of the reading habit in students is favored.
Keywords: Habit; Interactive Reading; comprehension; promotion; Conventional space